2014
DOI: 10.3168/jds.2014-8020
|View full text |Cite
|
Sign up to set email alerts
|

Development and shelf-life determination of pasteurized, microfiltered, lactose hydrolyzed skim milk

Abstract: The segment of the world population showing permanent or temporary lactose intolerance is quite significant. Because milk is a widely consumed food with an high nutritional value, technological alternatives have been sought to overcome this dilemma. Microfiltration combined with pasteurization can not only extend the shelf life of milk but can also maintain the sensory, functional, and nutritional properties of the product. This studied developed a pasteurized, microfiltered, lactose hydrolyzed (delactosed) sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 17 publications
4
10
0
Order By: Relevance
“…Several authors have found total bacterial reductions within the range of 4-5 log CFU mL -1 , which are directly related to initial contamination levels, operating parameters, and membrane characteristics (Antunes et al, 2014;Rezzadori et al, 2014). The results of this experiment are consistent with results in many studies, since lower counts were observed for mesophilic aerobic bacteria and yeasts, which were higher in numbers before MF (Table 1).…”
Section: Microbial Countssupporting
confidence: 82%
“…Several authors have found total bacterial reductions within the range of 4-5 log CFU mL -1 , which are directly related to initial contamination levels, operating parameters, and membrane characteristics (Antunes et al, 2014;Rezzadori et al, 2014). The results of this experiment are consistent with results in many studies, since lower counts were observed for mesophilic aerobic bacteria and yeasts, which were higher in numbers before MF (Table 1).…”
Section: Microbial Countssupporting
confidence: 82%
“…Horner et al [19], using commercial Kluyveromyces    β -galactosidases in 3, 6, 9, and 12 U/mL concentrations, at 2°C after 48 h of reaction, verified values of approximately 100% lactose hydrolysis efficiency for pasteurized milk. Antunes et al [23] evaluated the physicochemical, microbiological, and sensorial characteristics of delactosed milk using 20 U/mL of the K. lactis    β -galactosidase enzyme at 10°C. Under these conditions, the authors verified a hydrolysis rate of 90% in 21 h of reaction.…”
Section: Resultsmentioning
confidence: 99%
“…The browning level depends on the hydrolysis percent (Rehman, 2009). In addition, when lactose is hydrolysed, the number of free molecules actually increases, thus raising the amount of soluble substances in the milk, decreasing its freezing point (Antunes et al, 2014). Lactose-hydrolysed milk also presents a higher sweetness due to the lower sweetness of lactose compared with its monosaccharide constituents, glucose and galactose.…”
Section: Accepted Manuscriptmentioning
confidence: 99%